Associations of Insulin Resistance With Systolic and Diastolic Blood Pressure: A Study From the HCHS/SOL. Issue 3 (12th August 2021) - Quesada, Odayme; Claggett, Brian; Rodriguez, Fatima; Cai, Jianwen; Moncrieft, Ashley E.; Garcia, Karin; Del Rios Rivera, Marina; Hanna, David B.; Daviglus, Martha L.; Talavera, Gregory A.; Bairey Merz, C. Noel; Solomon, Scott D.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Insulin resistance is hypothesized to contribute to increases in blood pressure (BP) through both the renin-angiotensin-aldosterone and sympathetic nervous systems. Prior large-scale studies examining this association are confounded by overt diabetes, obesity, and antihypertensive medication use. In a cross-sectional analysis of 10 810 HCHS/SOL (Hispanic Community Health Study/Study of Latinos) participants without diabetes and not taking antihypertensive medications, we examined the associations of insulin resistance, quantified by homeostasis model assessment of insulin resistance (HOMA-IR), with systolic BP (SBP) and diastolic BP overall and stratified by sex and prediabetes status in unadjusted and adjusted analyses. The total sample included 52% women; mean (SD) age, 37.2 (13.4) years; 39% of participants had prediabetes (mean [SD] HOMA-IR, 2.8 [2.2]). Stage 1 or 2 hypertension was present in 26% of participants (mean [SD] SBP, 116.8 [15] mm Hg and diastolic BP, 71.0 [10.4] mm Hg). Overall, there was a significant linear association between HOMA-IR and both SBP (β, 2.64±0.44) and diastolic BP (β, 1.49±0.35). We found a significant interaction with sex and the association between HOMA-IR and SBP; the association was linear in men and nonlinear in women. There was no statistically significant interaction between prediabetes status and the associations between HOMA-IR and BP. In conclusion, in a large community-based sample of Hispanic/Latino adults of diverse national backgrounds not taking antihypertensive medications and free from diabetes, insulin resistance was positively associated with both SBP and diastolic BP. Future longitudinal studies, with adequate power to examine sex-specific differences, are needed to examine the independent contribution of insulin resistance to the development of hypertension.